Bleaching toothpaste with two different concentrations of hydrogen peroxide: A randomized double-blinded clinical trial. (December 2020) - Kim, Hyun-Jung; Jang, Ji-Hyun; Choi, Dongseok; Kim, Jei; Shim, Ji-Hee; Kim, Duck-Su
Abstract: Objectives: This randomized double-blinded clinical trial evaluated the bleaching efficacy and incidence of contact hypersensitivity of three kinds of bleaching toothpaste. Methods: Forty-nine participants above A2 shade on the maxillary central incisor (#11) and canine (#13) were randomized into three groups: TW group (n = 15), 0.75 % HP-containing toothpaste (Toothwhole white); VL group (n = 15), 0.75 % HP-containing toothpaste (Vussen 7); and VH group (n = 17), 2.8 % of HP-containing toothpaste (Vussen 28). Participants were instructed to manually brush their teeth for 3 min, 3 times per day for 12 weeks. They were followed-up after 4 and 12 weeks. Shade measurements were performed using a spectrophotometer (SP), and data were calculated with CIELab ( Δ E a b * ) and CIEDE2000 ( Δ E 00 ) formula. Additionally, visual inspection (VI) using the Vitapan classical shade guide was also performed, and the correlation between the two measurements was analyzed by comparing the CIELab ( Δ E a b * ) values. The incidence of contact hypersensitivity at each follow-up was recorded. A mixed-effect model was performed to assess shade changes and chi-square tests for the incidence of contact hypersensitivity, respectively. Results: At 12 week follow-up, all groups showed Δ E a b *   above 3.46, and Δ E 00 above 2.25 for tooth #11. For tooth #13, the Δ E a b * and Δ E 00 of VH and TW groups only were above those thresholds. Shade change varied according to toothpaste and follow-up points. SP and VI showed a moderate positive correlation for L*, a*, and b*, respectively ( P  < 0.05). Contact hypersensitivity was not significantly different among the groups ( P  > 0.05). Conclusions: Bleaching toothpaste with higher HP yields a better shade change than other toothpaste after 12 weeks. Clinical significance: The use of bleaching toothpaste with a higher HP concentration results in a better shade improvement.